Natural products targeting RAS by multiple mechanisms and its therapeutic potential in cancer: An update since 2020 - Yanqing Liu; Jie Chen; Xiang Li; Yu Fan; Cheng Peng; Xiaochun Ye; Yingshuang Wang; Xin Xie (Pharmacological Research)
RAS proteins, as pivotal signal transduction molecules, are frequently mutated and hyperactivated in various human cancers, closely associated with tumor cell proliferation, survival, and metastasis. Despite extensive research on RAS targeted therapies, developing effective RAS inhibitors remains a significant challenge. Natural products, endowed with unique chemical structures and diverse biological activities through long-term natural selection, have emerged as a vital resource for discovering novel RAS-targeted therapeutic drugs. This review focuses on the latest advancements in targeting RAS with natural products and categorizes these natural products based on their mechanisms of action. Additionally, we discuss the challenges faced by these natural products during clinical translation, including issues related to pharmacokinetics. Strategies such as combination therapy, structural optimization, and drug delivery systems are anticipated to enhance efficacy and overcome these challenges.